Planting season influence in height growth and in rust intensity in monoprogenies and clones of Eucalyptus urograndis - Abilio, Fernanda Maria; Passos, José Raimundo [UNESP]; De Moraes, Cristiano Bueno [UNESP]; Furtado, Edson Luiz (Instituto de Pesquisa e Estudos Florestais (IPEF), 2018)
Rust is among the main diseases which may affect the wood availability and production cost of eucalyptus plantations. Eucalyptus genetic improvement for resistance to rust and plant growth study in different planting seasons and sites are silvicultural strategies which may reduce damage. The aim of this study was to evaluate the resistance to rust and the initial height growth of eucalyptus monoprogenies and clones by breeding method and genotype in different planting season. Two experiments were established in the county of Avare/SP in Summer and Winter to evaluate the rust incidence and severity in plants up to 18 months old in different planting seasons. The initial growing in plant height was measured on the 150th and 360th day after planting and calculated the height increment and the coefficient of variation. The statistical design was randomized blocks with two monoprogenies and two hybrid clones of E. grandis x E. urophylla, four replications and 300 plants per plot. The winter planting presented the lowest incidence to rust and was 31.17% higher than summer planting. The monoprogenies and clones by breeding method did not present statistical differences in the incidence of rust and the monoprogeny's height on the 360th day was - 13.62% compared to clonal; the genotypes maintained the same characteristics for susceptibility to fungus as their parents and there were no significant differences in height. Winter planting is a management practice for escaping to rust and to achieve a better initial growth of Eucalyptus urophylla x E. grandis, and the clones are an alternative in areas with rust incidence.
Influência da época de plantio no crescimento em altura e na intensidade da ferrugem em monoprogênies e clones de Eucalyptus urograndis
Keywords: Clone; Eucalyptus; Forest improvement; Initial growth; Monoprogeny; Puccinia psidii